Validity and reliability of the My Jump 2 app for detecting interlimb asymmetry in young female basketball players - Nenad Stojiljković; Dušan Stanković; Vladan Pelemiš; Nebojša Čokorilo; Mihai Olanescu; Miruna Peris; Adrian Suciu; Alin Plesa (Frontiers Media S.A., 2024)
IntroductionThe aim of this study was to examine the validity and reliability of the My Jump 2 app for the assessment of interlimb jump asymmetry in young female basketball players.MethodsNine athletes (age 15 ± 0.9 years; weight 62.9 ± 5.8 kg; height 173.6 ± 6.1 cm) performed single-leg drop jumps (DJs) and both-leg drop jumps on a force plate (Kistler Quattro jump) and were simultaneously recorded on two smartphones using the My Jump 2 app. Jump height from flight time and contact time data were statistically analyzed to evaluate the validity of two different camera settings, drop jump performance, and interlimb jump asymmetry in basketball players. The testing was repeated after 1 week for test retest reliability.ResultsHigh test-retest reliability [intraclass correlation coefficient (ICC) > 0.88] was observed in DJ height. High correlation between the force plate and the My Jump 2 app was observed in DJ height (r = 0.99) and DJ contact time (r = 0.98). For the interlimb jump height asymmetries, mean differences were 0.6 percentages for the My Jump 2 app and the force plate, respectively (p = 0.77). Inter-device reliability revealed almost perfect correlation for the DJ height (ICC = 0.99, r = 0.98).ConclusionThe My Jump 2 app is a valid and reliable tool to assess drop jump performance and interlimb asymmetry in young female basketball players.